Relationship between Dietary Diversity and Central Obesity in Adults Aged 18–65 Years: A Cross-Sectional Study in Chongqing, China - Huang, Mingyu; Bai, Ruixue; Shah, Tayyib; Zhang, Yong (British Journal of Healthcare and Medical Research, 2026)
Aim: Dietary diversity is considered a key component of a healthy diet, as it ensures the intake of a wide range of nutrients, which help maintain normal metabolic functions. This study aims to explore the relationship between dietary diversity and the prevalence of central obesity in adults aged 18–65 years, as well as the associated factors in the adults aged 18–65 years. Methods: A cross-sectional study was conducted in a health center that included adults aged 18–65 years. Dietary intake information was obtained using the food frequency questionnaire, and physical examination data were obtained from their health examination reports. The dietary diversity score is calculated by adding up the scores for the types of foods consumed. Logistic regression was used to analyze the association between dietary diversity score and central obesity, with adjustment for confounding factors and stratified analysis. Results: Among 833 individuals, central obesity was 144 (17.29%). In the fully adjusted model, total dietary diversity score (OR=0.89, 95% CI: 0.80 0.98) and plant-based dietary diversity score (OR = 0.87, 95% CI: 0.76 0.99) was associated with a reduced risk of central obesity. The higher the DDS, the lower the risk of central obesity. Additionally, stratified analysis revealed that dietary diversity scores among different genders and ages were associated with the risk of central obesity. Conclusions: The results of this study indicate that dietary diversity is a protective factor for central obesity, and adopting a diversified diet may reduce the risk of central obesity in the.